Supporting software architects to improve their software system's decomposition – lessons learned. Issue 3 (19th October 2011) - Vanya, Adam; Klusener, Steven; Premraj, Rahul; van, Hans
SUMMARY The architect of a large, evolving system may wish to revise its decomposition from time to time; for instance, because the structure has deteriorated over time, certain components need to be outsourced to another site. One way to assess the current decomposition is to consider the past evolution, searching for components that often changed together. We iteratively devised and implemented a process for doing so at Philips Healthcare MRI. In this paper, we describe the lessons learned on how to effectively support architects to improve their system decomposition. Copyright © 2011 John Wiley & Sons, Ltd.